Primary closure combined with C-tube drainage through cystic duct after laparoscopic common bile duct exploration is safe and feasible for patients - Sui, Xin; Sui, Zhenghui; Gu, Xingwei; Ding, Mingjin; Miao, Ganggang (Frontiers in Surgery, 2022)
Objective Biliary duct management is of great significance after laparoscopic cholecystectomy (LC) combined with laparoscopic common bile duct exploration (LCBDE) in the treatment of cholecystolithiasis accompanied with common bile duct (CBD) stones. This study is to evaluate the safety and effectiveness of primary closure with C-tube drainage through cystic duct after LC + LCBDE. Methods Through a retrospective study, 290 patients who underwent LC + LCBDE in our hospital from January 2019 to April 2022 were enrolled and divided into 2 groups. 143 patients underwent primary closure with C-tube drainage through cystic duct (C-tube group) and the other 147 patients underwent traditional T-tube drainage (T-tube group). Personal information, perioperative examinations, surgical results, and follow-up results were collected and analyzed. Results There were no significant differences in the average age, gender, the mean of CBD diameters and the rate of comorbidities (acute cholecystitis, obstructive jaundice, acute pancreatitis and acute cholangitis) between the two groups (P > 0.05). Hospital stay, postoperative hospital stay were significantly shorter in the C-tube group than T-tube group (P < 0.05). In addition, the average time of placing and removal the drainage tubes was significantly less than those of the T-tube group (P < 0.05). This study also showed significant differences in the incidence of postoperative abdominal infection and soft tissue infection in the two groups (P < 0.05). There were no significant differences in the incidence of postoperative complications including cholangitis, bile duct stenosis, mortality in two groups. There were also no significant differences between the two groups of the recurrence of CBD stones, reoperation and readmition in 30 days during the median follow-up of 6 months. Conclusions Compared with T tube drainage, patients with C-tube drainage after LC + LCBDE with primary closure of cystic duct recovered faster and had fewer complications. C-tube drainage is a safe and feasible treatment option for patients with cholecystolithiasis and choledocholithiasis.